2016
DOI: 10.3329/bmrcb.v41i2.29991
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and resistance profile of nosocomial Acinetobacter baumannii in intensive care unit of tertiary care hospital in Bangladesh

Abstract: This study was designed to investigate the resistance profile along with the genetic background of resistance to beta-lactam antibiotics among the nosocomial A. baumannii in Bangladesh. A. baumannii was confirmed by detecting blaOXA-51-like. Antibiotic susceptibility was determined by disk diffusion method. Agar dilution method was used to determine MIC of ceftazidime and imipenem. All A. baumannii were phenotypically screened for ampC, ESBL and MBL production. Genetic markers of antibiotic resistance such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…27 A study conducted at the Dhaka Medical College Hospital (DMCH) showed 96% strains of A. baumannii isolated from endotracheal aspirates collected from patients, were multidrug resistant. 28 Another study carried in Square Hospitals Ltd. showed 90 % of the A. baumannii strains isolated from the patients with lower respiratory tract infections, were multidrug resistant. 29 In this study, 57% A. baumannii were MDR and 29% were XDR indicating an alarming situation.…”
Section: Discussionmentioning
confidence: 99%
“…27 A study conducted at the Dhaka Medical College Hospital (DMCH) showed 96% strains of A. baumannii isolated from endotracheal aspirates collected from patients, were multidrug resistant. 28 Another study carried in Square Hospitals Ltd. showed 90 % of the A. baumannii strains isolated from the patients with lower respiratory tract infections, were multidrug resistant. 29 In this study, 57% A. baumannii were MDR and 29% were XDR indicating an alarming situation.…”
Section: Discussionmentioning
confidence: 99%
“…One more study examined endotracheal aspirates among patients of ICU reported that 96% of Acinetobacter baumannii were multidrug-resistant. The AMR (Antimicrobial resistance) genes such as bla ampC and carbapenemase genes ( bla MBLs and bla KPC ) were found in 95.83%, and 100% of A. baumanni were cephalosporin and imipenem resistant, respectively [63]. After that, the current study showed the MBL-producing gram-negative microorganism presence through multiplex PCR among VAP patients were most likely.…”
Section: Discussionmentioning
confidence: 62%
“…baumannii is an important nosocomial pathogen in healthcare facilities and has become one of the most significant microorganisms causing infections in hospitalized patients in last few decades [28]. A study conducted at the Dhaka Medical College Hospital (DMCH) showed 96% strains of A. baumannii isolated from endotracheal aspirates collected from patients, were multidrug resistant [29]. Another study carried in Square Hospitals Ltd. showed 90 % of the A. baumannii strains isolated from the patients with lower respiratory tract infections, were multidrug resistant [30].…”
Section: Discussionmentioning
confidence: 99%